2014
DOI: 10.1038/ijo.2014.185
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory characteristics of adipose tissue collected by surgical excision vs needle aspiration

Abstract: Subcutaneous adipose tissue can be obtained for research during an elective, clinically indicated operation by standard surgical excision approaches and by needle aspiration in pure research settings. Whether measurements of inflammatory markers and cells made in tissue collected these two different ways are comparable is debatable. We sought to determine whether these two techniques yield systematically different results for measurements of inflammation, cellular senescence, and adipose tissue composition. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…A further limitation could be the size of the biopsy, as it have been shown that the subcutaneous needle biopsy might be too little, compared with a surgical biopsy [43]. However in a currently published paper by Santosa et al [44] the examination of cytokines seems feasible I fine needle biopsies like used in the present study, and as support for the present data we were able to measure cytokines in most samples.…”
Section: Discussionsupporting
confidence: 47%
“…A further limitation could be the size of the biopsy, as it have been shown that the subcutaneous needle biopsy might be too little, compared with a surgical biopsy [43]. However in a currently published paper by Santosa et al [44] the examination of cytokines seems feasible I fine needle biopsies like used in the present study, and as support for the present data we were able to measure cytokines in most samples.…”
Section: Discussionsupporting
confidence: 47%
“…These methods do not result in any differences when examining adipose tissue characteristics according to a recent study. 98 Some investigations have found two distinct pools of fat cell sizes in the same subject whereof one pool consists of very small fat cells. 99,100 Surprisingly, a pool of very small fat cells have been found in subjects with adipose inflammation and insulin resistance 99,101 These very small fat cells, with a diameter of 20-50 µm might be missed with the method we used to isolate fat cells.…”
Section: Isolation Of Fat Cellsmentioning
confidence: 99%
“…ScAT and VAT (corresponding to PtAT, in the present study scenario) are very distinct, so differences in gene and protein expression profiles may contribute to the observed disturbances. Different fat depots differ in cell size, physiological function, and contribution to disease states ( 49 ). In VAT, adipocytes have greater lipolytic activity and generally secrete more pro-inflammatory cytokines than ScAT, contributing to systemic inflammation associated with metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%